Deuterium retention in tungsten fiber-reinforced tungsten composites. (June 2021) - Kärcher, A.; Riesch, J.; Almanstötter, P.; Manhard, A.; Balden, M.; Coenen, J.W.; Hunger, K.; Maier, H.; Raumann, L.; Schwalenberg, D.; Neu, R.
Highlights: Preparation of purpose-built samples of tungsten fibre reinforced tungsten. Laterally resolved measurements of surface deuterium retention in W fibre reinforced W. Quantitative comparison of deuterium retention of W fibre reinforced and power metallurgical W. Identification of D retention mechanisms. Abstract: In future fusion reactors, plasma-facing materials (PFMs) have to withstand unique conditions such as high temperatures, ion and neutron irradiation. Tungsten (W) has been established as main candidate material due to its favorable properties regarding the fusion environment but brings one major challenge: Its brittleness at moderate temperatures can lead to failure of tungsten components. Tungsten fiber-reinforced tungsten (Wf /W), a tungsten matrix containing drawn tungsten fibers, was developed to mitigate this problem by using extrinsic toughening mechanisms to achieve pseudo-ductility. The deuterium (D) retention in Wf /W manufactured by chemical vapor deposition (CVD) has been investigated using Wf /W single layered model systems consisting of a single plane of unidirectional tungsten fibers embedded in a tungsten matrix produced by CVD. Various parameters with potential influence on the D retention, such as the choice of an erbium oxide interface and potassium doping, have been included in the investigation. The samples have been ground to varying distances between surface and fiber plane - exposing distinct details of the Wf /W microstructures at the surface. The samples were exposed to a low temperature D plasma at 370 K for 72 h resulting in a total fluence of 10 25 D/m 2 . The D retention of all samples was measured by nuclear reaction analysis (NRA) and thermal desorption spectroscopy (TDS). The D retention in Wf /W composites is higher than in reference samples made from hot-rolled W by factors between 2 and 5. In addition, a comparison of NRA and TDS data indicates that D penetrates faster into the depth of Wf /W material than into hot-rolled tungsten.